2017
DOI: 10.1002/2016jg003714
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability in biogenic gas dynamics in a subtropical peat soil at the laboratory scale is revealed using high‐resolution ground‐penetrating radar

Abstract: The importance of peatlands as sources of greenhouse gas emissions has been demonstrated in many studies during the last two decades. While most studies have shown the heterogeneous distribution of biogenic gas in peat soils at the field scale (sampling volumes in the order of meters), little information exists for submeter scales, particularly relevant to properly capture the dynamics of hot spots for gas accumulation and release when designing sampling routines with methods that use smaller (i.e., submeter) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…MEGA also replicated two-dimensional gas storage down the length of the peat column, showing values similar to gas contents measured using GPR in the lab sample (Figures 4 and 2a). While recent studies have shown the heterogeneous lateral distribution of gases in subtropical peat samples from the Everglades at small (submeter) laboratory scales (Mustasaar & Comas, 2017), this study is to our knowledge the first attempt to measure and model variability of gas distribution with depth in subtropical peat. Areas of increased gas content 0.15-to 0.20-m thick were observed in both the lab sample (depth of 0-0.15, Figure 4) and in model domain (depths of 0.4-0.6 m in Figure 2a and 0.5-0.7 m in Figure 2b).…”
Section: Discussionmentioning
confidence: 98%
“…MEGA also replicated two-dimensional gas storage down the length of the peat column, showing values similar to gas contents measured using GPR in the lab sample (Figures 4 and 2a). While recent studies have shown the heterogeneous lateral distribution of gases in subtropical peat samples from the Everglades at small (submeter) laboratory scales (Mustasaar & Comas, 2017), this study is to our knowledge the first attempt to measure and model variability of gas distribution with depth in subtropical peat. Areas of increased gas content 0.15-to 0.20-m thick were observed in both the lab sample (depth of 0-0.15, Figure 4) and in model domain (depths of 0.4-0.6 m in Figure 2a and 0.5-0.7 m in Figure 2b).…”
Section: Discussionmentioning
confidence: 98%
“…Second, a nucleus may form in a small pore pocket under conditions of supersaturation, although the measured dissolved CH 4 concentration will only represent an “average” value for a much larger volume with mostly low CH 4 concentration. Furthermore, the CH 4 concentration in gas bubbles can vary substantially, e.g., between 9% and 77% over time (Mustasaar & Comas, ), suggesting significant heterogeneity in dissolved CH 4 concentration in pore water and frequent mass exchange between the gaseous phase and dissolved phase. Spatiotemporal variations in both dissolved and gaseous CH 4 concentration observed by Mustasaar and Comas () were ascribed to changes in CH 4 production within the peat sample, probably in relation to changes in plant composition and/or quality of organic matter content making up the hotspot area.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the CH 4 concentration in gas bubbles can vary substantially, e.g., between 9% and 77% over time (Mustasaar & Comas, ), suggesting significant heterogeneity in dissolved CH 4 concentration in pore water and frequent mass exchange between the gaseous phase and dissolved phase. Spatiotemporal variations in both dissolved and gaseous CH 4 concentration observed by Mustasaar and Comas () were ascribed to changes in CH 4 production within the peat sample, probably in relation to changes in plant composition and/or quality of organic matter content making up the hotspot area. Third, Boudreau () suggested that, as much sedimentary material is formed subaerially in terrestrial environments, trapping of gas during its formation is likely common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GPR method has been utilized in several studies for more than a decade to explore aspects of biogenic gas dynamics in peat soils, including field‐scale studies in boreal systems to investigate both its spatial (Comas et al, 2005a, 2005b; Comas & Slater, 2013; Parsekian et al, 2011; Strack & Mierau, 2010) and temporal distribution (Comas et al, 2007; Comas et al, 2008), as well as similar studies to understand gas dynamics in subtropical systems (Comas & Wright, 2014; Wright & Comas, 2016). Laboratory‐based studies have also been conducted using common offset measurements (Mustasaar & Comas, 2017) and ZOP measurements (Comas & Slater, 2007) to noninvasively monitor the internal biogenic gas dynamics of peat blocks similar to those used in this study. Compared to these studies, the uniqueness of the study presented here resides in the fact that we employ a combination of geophysical (i.e., GPR in transmission mode) and hydrological measurements on peat monoliths while inducing changes in salinity via increased concentrations of NaCl.…”
Section: Methodological Backgroundmentioning
confidence: 99%